2014
DOI: 10.1038/bjc.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram predicting pulmonary metastasis of hepatocellular carcinoma following partial hepatectomy

Abstract: Background:Pulmonary metastasis (PM) following curative hepatectomy for hepatocellular carcinoma (HCC) is indicative of a poor prognosis. This study aimed to develop a nomogram to identify patients at high risks of PM.Methods:A primary cohort of patients who underwent curative hepatectomy for HCC at the Eastern Hepatobiliary Surgery Hospital from 2002 to 2010 was prospectively studied. A nomogram predicting PM was constructed based on independent risk factors of PM. The predictive performance was evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 31 publications
4
59
0
Order By: Relevance
“…Additionally, there is still no well-known predictive system based only on clinicopathological data for early recurrence. Although some nomogram-based systems using clinicopathological data have been proposed for predicting HCC recurrence (27)(28)(29)(30), their accuracy has been limited by the precision of physical markings. Therefore, these prediction systems have not been externally validated and have not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is still no well-known predictive system based only on clinicopathological data for early recurrence. Although some nomogram-based systems using clinicopathological data have been proposed for predicting HCC recurrence (27)(28)(29)(30), their accuracy has been limited by the precision of physical markings. Therefore, these prediction systems have not been externally validated and have not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…First proposed in 2006, decision curves have been used in cancer research [2][3][4][5][6] and many other fields. 7-11 For example, decision curves have evaluated models that predict lung cancer in high-risk populations which can then be used as tools for recommending computed tomography (CT) screening.…”
Section: Decision Curvesmentioning
confidence: 99%
“…There is then a suggestion that high-risk individuals are those whose risks are in this region of the plot. 4 This erroneous approach tends to lead to high risk thresholds, at least when a single risk model is compared with treat all and treat none.…”
Section: Decision Curves Cannot Be Used To Choose a Risk Thresholdmentioning
confidence: 99%
“…[14,25] Preoperative AFP has been incorporated in several prognostic nomograms for HCC as either a categorical variable or after a logarithmic transformation. [19,34,35] In this study, the AFP level was incorporated as a continuous variable because of its wide range in this cohort and its positive correlation with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…[14,16] Consistent with the present study, several studies reported MVI as an independent risk factor for prognosis and incorporated it into prognostic nomograms. [19,34,35,43,44] Nonencapsulated HCC was prone to direct liver invasion, tumor microsatellite formation, and vascular invasion. [45] Unfavorable outcomes were observed among patients with nonencapsulated HCC in most studies, which were in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%